The root microbiome: Community assembly and its contributions to plant fitness. Issue 2 (26th February 2022) - Bai, Bo; Liu, Weidong; Qiu, Xingyu; Zhang, Jie; Zhang, Jingying; Bai, Yang
Abstract: The root microbiome refers to the community of microbes living in association with a plant's roots, and includes mutualists, pathogens, and commensals. Here we focus on recent advances in the study of root commensal community which is the major research object of microbiome‐related researches. With the rapid development of new technologies, plant–commensal interactions can be explored with unprecedented breadth and depth. Both the soil environment and the host plant drive commensal community assembly. The bulk soil is the seed bank of potential commensals, and plants use root exudates and immune responses to build healthy microbial communities from the available microbes. The plant microbiome extends the functional system of plants by participating in a variety of processes, including nutrient absorption, growth promotion, and resistance to biotic and abiotic stresses. Plants and their microbiomes have evolved adaptation strategies over time. However, there is still a huge gap in our understanding of the regulatory mechanisms of plant–commensal interactions. In this review, we summarize recent research on the assembly of root microbial communities and the effects of these communities on plant growth and development, and look at the prospects for promoting sustainable agricultural development through the study of the root microbiome. Abstract : Plant roots harbor a taxonomically defined microbial community (root microbiome), the assembly of which is influenced by soil environment and host plant. The root microbiome extends the functional system of plants by participating in a variety of processes, including nutrient absorption, growth promotion, and resistance to biotic and abiotic stresses.